2015
DOI: 10.1089/ars.2015.6299
|View full text |Cite
|
Sign up to set email alerts
|

The HMGB1-RAGE Inflammatory Pathway: Implications for Brain Injury-Induced Pulmonary Dysfunction

Abstract: Targeting the HMGB1 signaling axis may increase the number of lungs available for transplantation and improve long-term benefits for organ recipient patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 143 publications
0
47
0
2
Order By: Relevance
“…The rapid induction of surface RAGE by 7 d US could result from the persistent elevation of RAGE mRNA expression. RAGE up-regulation and signaling has been implicated in the development and progression of several inflammatory and neurodegenerative diseases (75–85), many of which show high levels of comorbidity with depression. However, this is the first report of long-term, persistent elevated hippocampal RAGE expression in the brain following chronic psychological stress exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid induction of surface RAGE by 7 d US could result from the persistent elevation of RAGE mRNA expression. RAGE up-regulation and signaling has been implicated in the development and progression of several inflammatory and neurodegenerative diseases (75–85), many of which show high levels of comorbidity with depression. However, this is the first report of long-term, persistent elevated hippocampal RAGE expression in the brain following chronic psychological stress exposure.…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 can bind to both TLR4 and RAGE and has been extensively reviewed by Weber et. al [19]. Their binding abilities depend on the redox states of HMGB1 [19].…”
Section: Introductionmentioning
confidence: 99%
“…al [19]. Their binding abilities depend on the redox states of HMGB1 [19]. The reduced form contains a thiol group at all three cysteine residues with a serum half-life of 17 min.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies have shown that cognitive deficit is 28 associated with increased neuroinflammation (oxidative-nitro-29 sative stress, TNF-a, IL-1b, and TGF-b1) in both cerebral cortex and 30 hippocampus of ethanol-exposed rats (Tiwari and Chopra, 2012). 31 As cell types of inflammation responding to injury in the brain, it 32 has been long thought that microglial cells are the major CNS (Nadatani et al, 2013;Weber et al, 2015). It has been suggested 57 that brain HMGB1 is highly expressed in neurons and is released 58 from neurons .…”
mentioning
confidence: 99%